Validation of the Korean Version of the Clinical Assessment Interview for Negative Symptoms - Jang, Seon-Kyeong; Park, Seon-Cheol; Choi, Kee-Hong; Yi, Jung-Seo; Park, Joong-Kyu; Lee, Jung Suk; Lee, Seung-Hwan (Psychiatry Investigation, 2017)
Clinical Assessment Interview for Negative Symptoms (CAINS) has recently been developed to improve measurement of negative symptoms in schizophrenia. We performed a multi-center study to validate the Korean version of the CAINS (CAINS-K) and explore potential cultural variation. One hundred eighty schizophrenia patients diverse in demographic and illness profile were recruited from four centers in Korea. Along with the CAINS-K, the Scale for the Assessment of Negative Symptoms (SANS), Brief Psychiatric Rating Scale (BPRS), Calgary Depression Scale for Schizophrenia (CDSS), a self-report measure of behavioral inhibition and activation (BIS/BAS) and neurocognitive tasks were administered to verify external validities. The CAINS-K showed high internal-consistency (0.92) and inter-rater reliability (0.77). Exploratory Factor Analysis replicated a two-factor structure of the original scale including motivation/pleasure and expression deficits dimensions. Korean patients tended to report lower pleasure compared to American patients in the prior study. The CAINS-K showed an adequate convergent validity with the SANS, negative symptoms of the BPRS, and BAS. A divergent validity was supported as the CAINS-K showed zero or only weak correlations with other symptoms of the BPRS, depression from the CDSS, and neurocognitive tasks. The CAINS-K demonstrated high internal consistency and adequate external validities, and is expected to promote studies on negative symptoms in Korean patients with schizophrenia.